INTERRELASI ANTARA PENGAMBILAN RISIKO, BERSAING AGRESIF MENGEJAR PRESTASI, DAN PROAKTIF SERTAPENGARUHNYA TERHADAP KECERDASANENTREPRENEURIAL DAN KEPUASAN KERJA (Studi Pada Perwira Menengah di Markas Besar TNI AL Cilangkap - Jakarta) - Akhmad Tarmizi (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2017)
Basically, job satisfaction is an individual thing. Each individual member of the Indonesian National Army - Navy will have a level of satisfaction varies according to the value system that applies to him. This study aimed to analyze how the mutual relationship between risk taking, compete aggressively pursue achievement, and a proactive attitude and how they affect entrepreneurial intelligence and job satisfaction of the middle-Navy officer (rank of Major and Lieutenant-Colonel) in the environment MABESAL Cilangkap - Jakarta. Sampling was addressed to 150 people Major and Lieutenant-Colonel of 100 people (men) from the existing amount. Of the 5 main variables of the study (risk taking, compete aggressively pursue achievement, proactive, entrepreneurial intelligence, and job satisfaction) raised 50 manifest variables or observations. The number of valid questionnaires were further processed as many as 250 copies. The data were processed with descriptive analysis, cross tabulation analysis, confirmatory factor analysis, analysis of the structural model , are summarized end with the test of the hypothesis. The results that test the 7th hypothesis proved significantly. Factors of risk taking, compete aggressively pursue achievement, and proactive significantly influence entrepreneureurial intelligence. Factors of risk taking, compete aggressively pursue achievement, and proactive also significantly influence job satisfaction. Entrepreneurial intelligence factors significantly influence job satisfaction. Further discussion of the recommendations for improvement and development potential risk taking, compete aggressively pursue achievement, proactive, entrepreneurial intelligence, and job satisfaction in MABESAL environment.